A novel method for camera‐trapping small mammals. (24th June 2014) - MCCleery, Robert A.; Zweig, Christa L.; Desa, Melissa A.; Hunt, Rodney; Kitchens, Wiley M.; Percival, H. Franklin
ABSTRACT Camera traps have increased our knowledge of animal distribution, activity, and behavior, but they are rarely used for small mammal research. This is likely because there are few techniques to that allow for species identification, reduce disturbance of bait from non‐target animals (e.g., raccoon [Procyon lotor]), and that can be used in all environments. In this paper we present a small mammal camera‐trapping methodology, the Hunt trap, which was designed to 1) work in tidal environments, 2) eliminate capture myopathy, 3) allow for successful identification of small mammal species, and 4) allow for continued trapping after disturbance by non‐target species. We tested the Hunt trap in the Lower Suwannee National Wildlife Refuge, Florida, USA, during February 2012 to February 2013. Live traps are still the best option when individuals must be physically captured for marking, radiotagging, demographic studies, or physiological assessments. However, if such data are not required, the Hunt trap design is an excellent technique to monitor species diversity, community composition, habitat selection, and distribution with efficiency and minimal effort. Published 2014. This article is a U.S. Government work and is in the public domain in the USA.